A quantitative real-time PCR method for absolute telomere length. (May 2008) - O'Callaghan, Nathan J.; Dhillon, Varinderpal S.; Thomas, Philip; Fenech, Michael
Telomere shortening is an important risk factor for cancer and accelerated aging. Here we describe the development of a simple and reproducible method to measure absolute telomere length. Based on Cawthon's quantitative real-time PCR (qRT-PCR) assay, our method uses an oligomer standard that can be used to generate absolute telomere length values rather than relative quantification. We demonstrate a strong correlation between this improved method and the "gold standard" of telomere length measurement—terminal restriction fragment analysis (TRF) by Southern hybridization. The capability to generate absolute telomere length values should allow a more direct comparison of results between experiments within and between laboratories.